Antarctic Outline Chart / Publication of the Office of the Chief of Hydographic Service of the Navy (USSR) - United States. Hydrographic Office; (Washington, DC : U.S. Navy Hydrographic Office, 1959)
1st ed., 1955. New ed., 1958. Reproduced by the U.S. Navy Hydrographic Office (November 1959) from U.S.S.R. chart Map labels in Russian; Title and publication information in English and Russian; Shows limit of ice shelf.; Includes sheet coverage key.; "U.S.S.R. 334" -- margins Grayscale; 1:17,000,000